Relacja „teologia-literatura piękna” w ujęciu historycznym - Szymik, Jerzy (Śląskie Studia Historyczno-Teologiczne, 1991)
Connections between theology and belles–lettres have a long history lasting more than 2000 years. Their roots ought to be sought in Pauline writings, whose author quotes and interprets the texts of Aratos of Soloi, Menandros and Epimenides of Knossos. Most writings of the patristic period tend to maintain an apologetic attitude towards lay literature. But at the same time there is evidence of theoretical and practical sympathy that the Fathers of the Church felt towards „pagan books”, to be found in Clement of Alexandria’s idea of „kosmika paidea”, St. Augustine’s pastoral advice as well as that of Jerome’s and Basil the Great’s, but most of all in the use non-Christian literature as „praeparatio evangelica”, propounded by Eusebius of Caesarea. Scholastic theology, which stressed rational perfection of theological discourse regarded literature (especially poetry) as „the lowest of all philosophical exercises” (Albertus Magnus). And yet even the mediaeval approach, exemplified by Thomas Aquinas, Alanus ab Insulis and monastic theology perceived in poetry important allegorical and symbolic values. A real split took place at the time of post-Tridentine theology, based on extremely rational philosophy of the Enlightenment, which rejected all kinds of „literariness” or „poetry making”. On the other side was the literature which more and more often negated the contents and values of Christian preaching. It is only in the epoch of the Vatican Council II that we witness a return to ancient closeness, cooperation and creative dialogue; as inspirations of litary nature have been functioning in the theologies of all times. The theology of so called „St. John’s description”, understood as „poetics of faith”, „poietic” theology are just a few selected examples. Theology and belles–lettres share twenty centuries of „historical experiences” rich in tension and dialogue. And they ought to become a foundation of fruitful interdisciplinary cooperation of post-Vatican Council theology and contemporary belles–lettres.